Will policies to promote energy efficiency help or hinder achieving a 1.5 °C climate target? - Patt, Anthony; van Vliet, Oscar; Lilliestam, Johan; Pfenninger, Stefan (Energy Efficiency, 2019)
There is a large literature suggesting that improvements in energy efficiency support efforts at climate mitigation. Addressing a conceptual gap in that literature, however, we evaluate whether there are any conditions under which policies to promote improvements in energy efficiency could be counterproductive to efforts to limit climate change to 1.5 °C global warming from pre-industrial times. We identify three conditions under which this could be the case. The first condition is if policies for energy efficiency have a political opportunity cost, in terms of crowding out or delaying policies aimed at decarbonizing energy supply. There is an extensive literature in the fields of political science and policy studies to suggest that this is possible, but there have been no studies examining whether it has actually happened or is likely to happen in the future. The second condition is if investments in energy efficiency improvements come at a higher cost, per unit of fossil energy avoided, than do investments in new renewable energy supply. Current cost estimates suggest that there are some energy efficiency investments for which this is the case, but it is difficult to predict whether this will remain the case in the future. The third condition is if policies for energy efficiency, or specific investments in energy efficiency, were to delay the complete decarbonization of energy supply by more than some critical value. We show that critical delay is quite short—measured in weeks to months—in the case of a 1.5 °C temperature target, assuming constrained availability of negative emission technologies. It is impossible to say whether any of these conditions is likely, but in theory, each of them would appear to be possible.
CRIS-Team Scopus Importer:2023-06-14
Keywords: Advocacy coalition framework; Climate change; Climate policy; Energy efficiency